Pendampingan Dan Pelatihan Penyusunan Laporan Keuangan Pada SD Muhammadiyah 8 Dan SMP Muhammadiyah 2 Kota Malang - Widyastuti, Aviani; Gina Harventy; Djoko Sigit Sayogo (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2023)
Until now, many schools do not understand how to prepare good and quality financial reports so that they can convey information properly to stakeholders. Lack of understanding due to the competency background possessed can also cause the resulting financial reports to also vary. This can be seen in SD Muhammadiyah 8 and SMP Muhammadiyah Malang City which have different financial reporting systems. On the other hand, as a subsidiary entity under the auspices of PDM Malang City, SD Muhammadiyah 8 and SMP Muhammadiyah 2 Malang City must report their financial reports to PDM so that consolidation can be carried out. This diversity of reporting systems also eventually led to problems for PDM Malang City. Based on this, to improve understanding and ability to produce uniform financial reports, it is necessary to carry out training and assistance on an excel-based financial reporting system as an approach method in solving existing problems.